2012
DOI: 10.1007/s00359-012-0735-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural coloration signals condition, parental investment, and circulating hormone levels in Eastern bluebirds (Sialia sialis)

Abstract: Many of the brilliant plumage coloration displays of birds function as signals to conspecifics. One species in which the function of plumage ornaments has been assessed is the Eastern bluebird (Sialia sialis). Studies of a population breeding in Alabama (USA) have established that plumage ornaments signal quality, parental investment, and competitive ability in both sexes. Here we tested the additional hypotheses that (1) Eastern bluebird plumage ornamentation signals nest defense behavior in heterospecific co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…The testosterone-treated birds preened more often in the spring than control birds; thus, preening is likely the mechanism behind this positive covariation. Overall, our data demonstrating that nestlings implanted with testosterone exhibit duller blue color corroborates the findings of a recent study of eastern bluebirds breeding in Oklahoma; adult males with less ornamented blue plumage (UV chroma and hue) had significantly lower androgen levels and higher corticosterone levels (Grindstaff et al 2012). The negative relationship that we found between testosterone treatment and the brightness of structurally based blue plumage could be either a direct consequence of testosterone on the development of feather nanostructure or an in-direct effect of the negative relationship between either testosterone or corticosterone and body condition.…”
Section: Discussionsupporting
confidence: 90%
“…The testosterone-treated birds preened more often in the spring than control birds; thus, preening is likely the mechanism behind this positive covariation. Overall, our data demonstrating that nestlings implanted with testosterone exhibit duller blue color corroborates the findings of a recent study of eastern bluebirds breeding in Oklahoma; adult males with less ornamented blue plumage (UV chroma and hue) had significantly lower androgen levels and higher corticosterone levels (Grindstaff et al 2012). The negative relationship that we found between testosterone treatment and the brightness of structurally based blue plumage could be either a direct consequence of testosterone on the development of feather nanostructure or an in-direct effect of the negative relationship between either testosterone or corticosterone and body condition.…”
Section: Discussionsupporting
confidence: 90%
“…In species with structural coloration, plumage variation results from differences in energy allocated to feather growth due to environmental conditions during molt, where birds that grow feathers faster have brighter, more ornamented feathers (Prum 2006, Siefferman et al 2008). Habitat quality, diet, social hierarchy, and parasite levels all can affect an individual's energy levels and thus feather growth, making it an honest signal since birds with large energy budgets can invest more in feather development (Hamilton and Zuk 1982, Grubb 2006, Hill 2006, Grindstaff et al 2012. Structural color could therefore result from and signal an individual's condition or resiliency to stressors Montgomerie 2003, Grindstaff et al 2012; but see Peters et al 2011), making it a useful indicator of individual and population health.…”
Section: Ornamentationmentioning
confidence: 99%
“…However, evidence for correlations between CORT and UV reflectance appear to be mixed. Henderson et al (2013) observed a negative correlation between UV color and baseline CORT in female Blue Tits, but this was not the case in Eastern Bluebirds, where a positive correlation existed between CORT and UV hue and saturation (Grindstaff et al 2012). In FSJs, Tringali and Bowman (2012) found that UV reflectance signals dominance in juveniles, and that the relative change in dominance was positively correlated with the relative difference in CORT (Tringali, pers.…”
Section: Stressmentioning
confidence: 99%
“…These studies support that melanin-based traits can also function as condition-dependent traits and, therefore, that different types of colours might share common evolutionary mechanisms. In this regard, recent studies investigating single ornaments of different species found that corticosterone levels (the main glucocorticoid released during stressful conditions in vertebrates; Wingfield et al, 1998) are linked to the expression of different types of colorations (Calisi & Hews, 2007;Loiseau et al, 2008;Roulin et al, 2008;Fitze et al, 2009;Lobato et al, 2010;Grindstaff et al, 2012;Mart ınez-Padilla et al, 2013). This suggests that stress hormones, which negatively affect condition in situations of long-term stress (Moore & Miller, 1984;Tokarz, 1987;Dhabhar & McEwen, 1997;Cote et al, 2010), may account for condition dependence of multiple types of ornaments in the same individual.…”
Section: Introductionmentioning
confidence: 99%